Finite Element Simulation of Opening Angle Response of Porcine Aortas Using Layer Specific GAG Distributions in One and Two Layered Solid Matrices - Noor M. Ghadie; Jean-Philippe St-Pierre; Michel R. Labrosse (Cardiovascular Engineering and Technology, 2025)
Purpose Recent studies have identified an effect of glycosaminoglycans (GAG) on residual stresses in the aorta, underscoring the need to better understand their biomechanical roles. Methods Aortic ring models for each of the ascending, arch and descending thoracic regions of the porcine thoracic aorta were created in FEBioStudio, using a framework that incorporates the Donnan osmotic swelling in a porous solid matrix. The distribution of fixed charge densities (FCD) through the thickness of the tissue was prescribed as calculated from experimentally quantified sulfated GAG mural distributions. Material parameters for the solid matrix, modeled using a Holmes–Mow constitutive law, were optimized using data from biaxial tensile tests. In addition to modelling the solid matrix as one layer, two layers were considered to capture the differences between the intima-media and the adventitia, for which various stiffness ratios were explored. Results As the stiffness of the adventitia with respect to that of the media increased, the simulated opening angle increased. The opening angle also decreased from the ascending to the descending thoracic region in both one- and two-layered solid matrices models. The simulated results were compared against the experimental contribution of GAG to the opening angle, as previously quantified via enzymatic GAG-depletion. When using one layer for the solid matrix, the errors between the simulated opening angles and the experimental contribution of GAG to the opening angle were respectively 28%, 15% and 23% in the ascending, arch and descending thoracic regions. When using two layers for the solid matrix, the smallest errors in the ascending and arch regions were 21% and 5% when the intima-media was modelled as 10 times stiffer, and as twice stiffer than the adventitia, respectively, and 23% in the descending thoracic regions when the intima-media and adventitia shared similar mechanical properties. Conclusions Overall, this study demonstrates that GAG partially contribute to circumferential residual stress, and that GAG swelling is one of several regulators of the opening angle. The minor discrepancies between simulated and experimental opening angles imply that the contribution of GAG extends beyond mere swelling, aligning with previous experimental indications of their interaction with ECM fibers in determining the opening angle.

Intramural Distributions of GAGs and Collagen vs. Opening Angle of the Intact Porcine Aortic Wall - Noor M. Ghadie; Jean-Philippe St-Pierre; Michel R. Labrosse (Annals of Biomedical Engineering, 2022)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

The Humphead Wrasse, Cheilinus Undulatus: Synopsis of a Threatened and Poorly Known Giant Coral Reef Fish - Y. Sadovy; M. Kulbicki; P. Labrosse; Y. Letourneur; P. Lokani; T.J. Donaldson (Reviews in Fish Biology and Fisheries, 2003)

Homotypic Interactions of Soluble and Immobilized Osteopontin - H. L. Goldsmith; J. M. Labrosse; F. A. McIntosh; P. H. Mäenpää; M. T. Kaartinen; M. D. McKee (Annals of Biomedical Engineering, 2002)